Building time architecture, event, and experience - Leatherbarrow, David 1953- (Bloomsbury Visual Arts, 2021)
"While most books on architecture concentrate on spatial themes, 'Building time' explores architecture's temporal dimensions. Through a series of close readings of buildings, both contemporary and classic, it shows why an understanding of time is critical to understanding good architecture. All buildings exist in time. Even if designed for permanence, they change, slowly but inevitably. They change use, they accrue history and meaning, they decay. Meanwhile, the sun traces a path in time through a building, as do the movements of the human body from room to room. Time, this book argues, is the framework for our spatial experience of architecture, and a key dimension of a building's structure and significance. Examining works by distinctive modern architects--from Eileen Gray to Álvaro Siza and Wang Shu--'Building time' is a book for theorists, designers, and anyone who wants to understand our experience of architecture. Through it, theorists will find a way to rethink the fundamental premise of design work, while designers will rediscover the order and ideas that shape the world around them--its buildings, interiors, and landscapes."--Page 4 of printed paper wrapper
Keywords: Zeit; Architektur; Philosophie; Umwelt; Architecture / Philosophy; Architectural design / Philosophy; Time / Social aspects; Architecture / Environmental aspects; Ellrichshausen, Pezo von; Fehn, Sverre / 1924-2009; Gray, Eileen / 1878-1976; Leonardo / da Vinci / 1452-1519; Maes, Nicolaes / approximately 1634-1693; Menzel, Adolph / 1815-1905; Moneo, José Rafael; Siza, Álvaro / 1933-; Wang, Shu / 1963-; Bo and Wohlert (Firm)